2019
DOI: 10.3390/e21111035
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Gravitation—From Black Hole Computers to Dark Energy and Dark Matter

Abstract: We show that the concept of entropy and the dynamics of gravitation provide the linchpin in a unified scheme to understand the physics of black hole computers, spacetime foam, dark energy, dark matter and the phenomenon of turbulence. We use three different methods to estimate the foaminess of spacetime, which, in turn, provides a back-door way to derive the Bekenstein-Hawking formula for black hole entropy and the holographic principle. Generalizing the discussion for a static spacetime region to the cosmos, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 91 publications
(147 reference statements)
1
8
0
Order By: Relevance
“…It is, finally, increasingly being suggested that the entropic structure of a BH may be more than a phenomenological correlate of its mass, possibly providing a route toward defining mass [65], specifying nontrivial internal topological structure [11], or even generating the phenomenology of dark energy or dark matter [66]. Theoretical investigation of the QRFs implemented by a BH may, therefore, offer exciting future developments.…”
Section: Discussionmentioning
confidence: 99%
“…It is, finally, increasingly being suggested that the entropic structure of a BH may be more than a phenomenological correlate of its mass, possibly providing a route toward defining mass [65], specifying nontrivial internal topological structure [11], or even generating the phenomenology of dark energy or dark matter [66]. Theoretical investigation of the QRFs implemented by a BH may, therefore, offer exciting future developments.…”
Section: Discussionmentioning
confidence: 99%
“…With such a review the experimental efforts dedicated to CRE could be prioritized accordingly so that appropriate detection and monitoring algorithms could be developed, including the alerting mechanisms on a sub-threshold level to be analyzed in accordance with the multi-messenger astrophysics strategies. The latter direction gives promising perspectives for new advances in astrophysics, reflected also in the new attention of theorists, also those addressing the questions related to space time structure (see e.g., [146][147][148]) and private interest in discussions (P. Homola's private communication with S. Carlip, Y. J. Ng, and Q. Wang.…”
Section: Uhecr As the Spacetime Structure Probe?mentioning
confidence: 99%
“…This is the space-time-matter foam which exists at the Planck scale: it represents Planck scale quantum dispersion and spontaneous localisation, which is equivalent to a stochastic oscillation of Planck scale curvature [curvature is of the order L 2 /L 4 p ]. The importance of Planck scale foam for the cosmological constant problem and for dark energy has been recently discussed also by [14][15][16]. In our theory, quantum gravity arises on time scales larger than Planck time, after coarse graining over Planck scale foam.…”
mentioning
confidence: 76%
“…This gives an extremely low mass density of the order of 10 −150 gm/cc. We now recall from recent discussion of the Karolyhazy uncertainty relation [12], and from the implied holography, that the universe has (R H /L p ) 2 ∼ 10 122 quanta of information [14]. Assuming one unit of information per elementary particle, we realise that ordinary matter contributes only a very small fraction to the information content, there being some 10 80 such particles.…”
mentioning
confidence: 98%